2022
DOI: 10.1088/1361-6463/ac9ec8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of binder-free SnO2NWs@C electrode and LiTFSI-based electrolyte for high-performance lithium-ion battery

Abstract: This study has investigated the effect of carbon coating on the electrochemical performance of SnO2 Nanowires (NWs) as an electrode along with a bis (trifluoromethane) sulfonimide lithium (LiTFSI)-based electrolyte in a lithium-ion battery (LIB). The vapor-liquid-solid (VLS) approach has been used to grow SnO2 NWs on the stainless steel mesh current collector. The obtained results have demonstrated that the utilization of the LiTFSI-based electrolyte improved the battery performance with the SnO2 NWs electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The MXene's surface was carbonized via a hydrothermal method using glucose [34,38,43]. First, 0.1 g of S-V-80 • C powder was dispersed in the mixture of 20 ml DI water and 5 ml Ethanol (Merk, 100 983) using magnetic stirring.…”
Section: Preparation Of Carbonized-mxenementioning
confidence: 99%
See 1 more Smart Citation
“…The MXene's surface was carbonized via a hydrothermal method using glucose [34,38,43]. First, 0.1 g of S-V-80 • C powder was dispersed in the mixture of 20 ml DI water and 5 ml Ethanol (Merk, 100 983) using magnetic stirring.…”
Section: Preparation Of Carbonized-mxenementioning
confidence: 99%
“…First, 0.1 g of S-V-80 • C powder was dispersed in the mixture of 20 ml DI water and 5 ml Ethanol (Merk, 100 983) using magnetic stirring. Then, 0.5 g of D-(+)-glucose monohydrate (Sigma-Aldrich 99.0% pure) was slowly dissolved into the suspension under stirring for 2 h. The solution was poured into the 100 ml Teflon-lined stainless-steel autoclave and heated at 170 • C for 24 h. Next, the suspension was washed several times with acetone [43]. Finally, the carbon-coated MXene (C@ S-V-80 • C) powder was dried at room temperature.…”
Section: Preparation Of Carbonized-mxenementioning
confidence: 99%
“…[7][8][9][10][11][12] In this regard, a great deal of research has been focused on creating batteries with increased specic energy, capacity, and safety. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] It has been proven that LIBs with silicon-based anodes are capable of supporting these benets if properly engineered, and therefore, aer an enormous amount of investment and research in this eld, they have now found their way into commercial LIBs. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Silicon-based anodes have been successfully employed in LIBs by nding solutions for their enormous volume change, unstable solid electrolyte interface (SEI) layer, and low electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%